2008
DOI: 10.1590/s0100-40422008000800014
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds in the thermoplastic extrusion of bovine rumen

Abstract: Recebido em 1/11/07; aceito em 12/6/08; publicado na web em 5/11/08The volatile compounds of raw and extruded bovine rumen, extracted by dynamic headspace, were separated by gas chromatography and analyzed by GC-MS. Raw and extruded materials presented thirty-two volatile compounds. The following compounds were identified in raw bovine rumen: heptane, 1-heptene, 4-methyl-2-pentanone, toluene, hexanal, ethyl butyrate, o-xylene, m-xylene, p-xylene, heptanal, limonene, nonanal, dodecane, tridecane, tetradecane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Further systematic studies are required to confirm the trends that were observed in this pilot study and to clarify their biochemical origin. Heptanal could be of endogenous origin, since it has been found in the headspace of bison muscle, bovine milk, and in raw and extruded bovine rumen . Octanal and acetophenone have been previously observed in bovine breath samples by others, 2-ethyl-1-hexanol have been detected in cattle rumen headspace, and benzaldehyde have been known to be present in dairy cows and/or their waste, consequently any of those materials could have metabolic relevance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further systematic studies are required to confirm the trends that were observed in this pilot study and to clarify their biochemical origin. Heptanal could be of endogenous origin, since it has been found in the headspace of bison muscle, bovine milk, and in raw and extruded bovine rumen . Octanal and acetophenone have been previously observed in bovine breath samples by others, 2-ethyl-1-hexanol have been detected in cattle rumen headspace, and benzaldehyde have been known to be present in dairy cows and/or their waste, consequently any of those materials could have metabolic relevance.…”
Section: Resultsmentioning
confidence: 99%
“…Heptanal could be of endogenous origin, since it has been found in the headspace of bison muscle, 1 bovine milk, 29 and in raw and extruded bovine rumen. 30 Octanal and acetophenone have been previously observed in bovine breath samples by others, 31 2-ethyl-1-hexanol have been detected in cattle rumen headspace, 32 and benzaldehyde have been known to be present in dairy cows and/or their waste, 33 consequently any of those materials could have metabolic relevance. Although these compounds cannot be attributed to a specific host/agent activity or response, the observed differences in the concentrations of the five statistically significant VOCs may reflect changes in VOC production related to the infection process.…”
mentioning
confidence: 91%
“…The volatile compounds were recovered by adsorption on Porapak Q polymer (80–100 mesh, Varian, Lake Forest, USA) by the technique of dynamic headspace, in accordance with the methodology described by Franco & Rodriguez‐Amaya (1983) and adapted by Silva et al. (2008).…”
Section: Methodsmentioning
confidence: 99%
“…b ) Sebanyak 0,1 g feses manusia sehat ditera dengan larutan garam fisiologis dan dihomogenkan dengan menggunakan vortex selama 10 detik. (Silva et al, 2008;Nurhayati, 2011). Sebanyak 1 mL cairan feses (10% b/v) dimasukkan ke dalam tabung eppendorf dan ditambahkan 0,003 g asam sulfo 5-salisilat dihidrat (Merck, Jerman).…”
Section: Analisis Profil Mikroflora Feses Relawan Manusia (Nurhayati unclassified